Changes of Numeraire for Pricing Futures, Forwards, and Options - Schroder, Mark (Review of Financial Studies, 1999)
[A change of numeraire argument is used to derive a general option parity, or equivalence, result relating American call and put prices, and to obtain new expressions for futures and forward prices. The general parity result unifies and extends a number of existing results. The new futures and forward pricing formulas are often simpler to compute in multifactor models than existing alternatives. We also extend previous work by deriving a general formula relating exchange options to ordinary call options. A number of applications to diffusion models, including stochastic volatility, stochastic interest rate, and stochastic dividend rate models, and jump-diffusion models are examined.]